Multimedia Interaktif Pengenalan Mamalia Indonesia Sebagai Tindakan Preventif Mencegah Kepunahan Metode MDLC - Halim Pratama, Muhammad Fajrul; Hanugrah Surya Purwaka; Dasril Aldo (JUPITER (Jurnal Penelitian Ilmu dan Teknologi Komputer), 2024)
Introduction to endangered mammals in Indonesia still only uses textbooks which are less effective and interesting. Then the lack of knowledge about Indonesian mammals which are threatened with extinction has resulted in a lack of awareness regarding these mammals, making the public less concerned about Indonesian mammals which are threatened with extinction. This research aims to design a learning media that introduces endangered Indonesian mammals with the hope of creating awareness about mammals. Using the Multimedia Development Life Cycle (MDLC) method which has stages of concept, design, material collection, assembly, testing and application distribution. The results obtained show that learning media applications consisting of text, images, sound and video can be accessed by users, especially children. The alpha and beta tests carried out obtained a score of 4.575 on a scale of 5, which indicates that the application is suitable for use. With this learning media, it is hoped that it can increase awareness of Indonesian mammals which are threatened with extinction. Keywords—Mammals, MDLC, Learning Media, Extinction